Fortifying boundaries - Olli Seuri; Pihla Toivanen (Journalistica, 2021)
This article examines how recent changes in the hybrid media environment have led media actors to define the “how and why” of their practices. We consider the discussion on the differences and similarities surrounding both the legacy media, and newcomers such as countermedia, to be part of journalism’s boundary work: the ongoing, yet temporally fickle, process of marking the boundaries between journalism and non-journalism. We demonstrate how both legacy and countermedia actors drew boundaries through vocabulary, institutional reflection, demarcation practices, and ethos. While the Finnish media underlined its institutional autonomy and dominance by defending the social good of journalism and dubbing countermedia as fake media, countermedia actor MV-lehti drew its own boundaries by ridiculing media professionals, media institutions, and journalists. Our findings illustrate how these actors consistently asserted the flawed ideological foundations of “the other”, with the consequence that boundaries have become fortified, rather than crossed or blurred.